Serum urea concentration and risk of 16 site-specific cancers, overall cancer, and cancer mortality in individuals with metabolic syndrome: a cohort study - E Wu; Guo-Fang Wei; Yang Li; Meng-Kai Du; Jun-Tao Ni (BMC Medicine)
Abstract Background The relationship between serum urea concentration and cancer in patients with metabolic syndrome (MetS) remains unclear. This study aimed to investigate the association between serum urea concentration and 16 site-specific cancers, overall cancer incidence, and cancer mortality in individuals with MetS. Methods We analysed the data of 108,284 individuals with MetS obtained from the UK Biobank. The Cox proportional hazards model was used to determine the association between serum urea concentration at recruitment and cancer. The Benjamini–Hochberg correction was used to account for multiple comparisons. Results Over the median follow-up period of 11.86 years, 18,548 new incident cases of cancer were documented. There were inverse associations of urea concentration with overall cancer incidence, and the incidence of oesophageal and lung cancers, with respective hazard ratios (95% confidence intervals) [HR (95% CI)] for the highest (Q4) vs lowest (Q1) urea quartiles of 0.95 (0.91–0.99), 0.68 (0.50–0.92), and 0.76 (0.64–0.90). However, high serum urea concentrations increased the male prostate cancer risk (HR 1.15; 95% CI 1.02–1.30). Although the Cox model indicated a protective effect of higher urea levels against stomach (HR 0.67; 95% CI 0.45–0.98; p = 0.040; FDR 0.120) and colorectal cancer (HR 0.86; 95% CI 0.74–0.99; p = 0.048; FDR 0.123), no strong evidence of association was found after applying the Benjamin-Hochberg correction. Moreover, across the median follow-up period of 13.77 years for cancer mortality outcome, 5034 cancer deaths were detected. An “L-shaped” nonlinear dose–response relationship between urea concentration and cancer mortality was discovered (p-nonlinear < 0.001), and the HR (95% CI) for urea concentration Q4 vs Q1 was 0.83 (0.77–0.91). Conclusions Serum urea concentration can be considered as a valuable biomarker for evaluating cancer risk in individuals with MetS, potentially contributing to personalised cancer screening and management strategies.